2018
DOI: 10.1002/ceat.201700314
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physical Adsorption of CO2 by Ionic Liquids‐Loaded Mesoporous Silica

Abstract: CO 2 sorption capacities of the neat and silica-supported 1-butyl-3-methylimidazolium-based ionic liquids (ILs) were measured under atmospheric pressure. The silica-supported ILs were synthesized by the impregnation-vaporization method and charactrized by N 2 adsorption/desorption and thermogravimeteric analysis (TGA). Evaluation of the effects of influential factors on sorption capacity demonstrated that by increase of the temperature, flow rate, and the weight percentage of ILs in sorbents, the sorption capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The main challenge to utilizing ILs for CO 2 capture is the high viscosity which results in severe mass transfer limitations, in addition to the cumbersome handling of liquids compared to solids on the small scale and in closed systems in terms of system complexity and maintenance (e.g., for applications requiring CO 2 filtration in spacecraft and submarines). To overcome these challenges, ILs have been loaded onto porous solid supports such as fumed silica, carbon, and polymeric membranes , which removes the necessity of pumping the absorbing liquid in a conventional absorber–desorber separation unit.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge to utilizing ILs for CO 2 capture is the high viscosity which results in severe mass transfer limitations, in addition to the cumbersome handling of liquids compared to solids on the small scale and in closed systems in terms of system complexity and maintenance (e.g., for applications requiring CO 2 filtration in spacecraft and submarines). To overcome these challenges, ILs have been loaded onto porous solid supports such as fumed silica, carbon, and polymeric membranes , which removes the necessity of pumping the absorbing liquid in a conventional absorber–desorber separation unit.…”
Section: Introductionmentioning
confidence: 99%
“…Under atmospheric pressure, Mirzaei et al. [ 82 ] examined the CO 2 sorption capabilities of silica-supported 1-butyl-3-methylimidazolium-based ionic liquids (ILs). It was discovered that [Bmim][BF 4 ] [Bmim][PF 6 ], and [Bmim][Tf 2 N] as a result of their high viscosities recorded decreased CO 2 capture at an increase in temperature from 25 °C to 50 °C.…”
Section: Future Prospects Of Membrane-ionic Liquid Technologies For C...mentioning
confidence: 99%
“…17−19 Some special ILs that interact with gas molecules mainly rely on the physical effect and structures and have advantages in the gas desorption process and the regeneration cycle. 20,21 1-Hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([HMIM][Tf 2 N]) is often used as a typical representative in the exploration of underlying absorption mechanisms because of its stability, low viscosity, and easy preparation. 22,23 Current pieces of experimental evidence have demonstrated that compared with traditional bulk ILs, nanoconfined ILs can effectively enhance gas absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…Various absorbents and technologies are constantly being developed to achieve effective emission reduction given the intense concern for global warming and air pollution problems. CO 2 and H 2 S are typical representatives of pollutant gases that widely exist in industrial production and even in the living environment. , Ionic liquids (ILs) have received more attention than traditional organic absorbents because of their many advantages as promising absorbents. For example, they are nonvolatile and do not easily cross-contaminate the gas vapor phase. Some special ILs that interact with gas molecules mainly rely on the physical effect and structures and have advantages in the gas desorption process and the regeneration cycle. , 1-Hexyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide ([HMIM]­[Tf 2 N]) is often used as a typical representative in the exploration of underlying absorption mechanisms because of its stability, low viscosity, and easy preparation. , …”
Section: Introductionmentioning
confidence: 99%